2014
DOI: 10.5817/cp2014-4-5
|View full text |Cite
|
Sign up to set email alerts
|

21st century media, fame, and other future aspirations: A national survey of 9-15 year olds

Abstract: Past research found that messages in popular television promote fame as a top value, while social media allow anyone to reach broad audiences (Uhls & Greenfield, 2011; Uhls & Greenfield, 2012). During a sensitive developmental phase, preteens are the largest users of media, consuming over seven-and-a-half hours a day, seven days a week, outside of school. A nationwide survey in the United States asked 315 youth (M = 12 years; range: 9 -15 years) about their media habits as well as their aspirations for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 55 publications
4
23
0
1
Order By: Relevance
“…To reconcile the media-empathy paradox, some social media researchers have emphasized specific online activities as an explanatory factor. For example, social digital interactions like chatting may be linked to higher empathy [20] [24]. Similarly, a meta-analysis of prosocial media suggests that exposure to prosocial media is linked to higher empathic concern and prosocial behaviors [25].…”
Section: Media-empathy Paradoxmentioning
confidence: 99%
“…To reconcile the media-empathy paradox, some social media researchers have emphasized specific online activities as an explanatory factor. For example, social digital interactions like chatting may be linked to higher empathy [20] [24]. Similarly, a meta-analysis of prosocial media suggests that exposure to prosocial media is linked to higher empathic concern and prosocial behaviors [25].…”
Section: Media-empathy Paradoxmentioning
confidence: 99%
“…Due to its nature, social media has been implicated in facilitating the rise of individualism through its encouragement of self-display and fameseeking. Indeed, research has demonstrated that social media is directly tied to self-focused aspirations such as fame, image, money and status (Uhls, Zgourou & Greenfield, 2014).…”
Section: Cultural Changes In Western Societymentioning
confidence: 99%
“…A follow-up survey of 9- to 15-year-olds showed that individualistic, self-focused aspirations, such as fame, were tied to watching TV, as well as to actively using a social networking site, a recipe for the narcissism that is part and parcel of the fame motivation. In contrast, collectivistic, other-focused aspirations were associated with older nontechnology activities, most of which were intrinsically social (Uhls, Zgourou, & Greenfield, 2014).…”
Section: Studies Of Social Cultural and Behavioral Change In The Unmentioning
confidence: 99%